If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = x + 39 Reorder the terms: 9 + 7x = x + 39 Reorder the terms: 9 + 7x = 39 + x Solving 9 + 7x = 39 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 7x + -1x = 39 + x + -1x Combine like terms: 7x + -1x = 6x 9 + 6x = 39 + x + -1x Combine like terms: x + -1x = 0 9 + 6x = 39 + 0 9 + 6x = 39 Add '-9' to each side of the equation. 9 + -9 + 6x = 39 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 39 + -9 6x = 39 + -9 Combine like terms: 39 + -9 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 12cosx=10 | | 5=20x | | 2p+7= | | 4x-120=-8x+60 | | 12n=10 | | -11(s-19)+12=-10 | | 49j+10j-49j-8j=94 | | 541-64n=-803 | | 4-3(x-5)=5x-13 | | 5-s=17 | | 0-3y=-19 | | 12/p | | x+(x*.2)=66 | | 67h-51h-15h+11=39 | | (2a+83)= | | -40+6x=68+2x | | 2g+5g+5=0 | | -24d+9d-(-97d)-78d-8d=80 | | y=4x^3-11x^2-43x-10 | | x^2+20+100= | | -6(r-11)-10=-34 | | 1/2v-3=19 | | -3x^5+2x^3=0 | | 17t+15t-19t-4t-6t+-17=16 | | 0x+1=4 | | Y=4x^2+6x+10 | | x*.2=66 | | -56u+52u+25=-99 | | 3x-2(-x+4)=x+4 | | 17t+15t-4t-6t+-17=16 | | -6(r+-11)+-10=34 | | -3x^5+2x^3=y |